'Ilm al-nafs fi al-thurath al-Islami - 'Abd al-Ḥamid, Ibrahim Shawqi; Najati, Muhammad'Uthman, 1914-; al-Sayyid,'Abd al-Halim Mahmud (al-Qahirah : al-Ma'had al-'Alami lil-Fikr al-Islami, 2008)
Compilation of studies interspersed with the text of classic tracts & excerpts on psychology within the Islamic tradition
Keywords: Psychology -- History; Psychology and religion; Islam -- Psychology